Testing taxpayers' cognitive abilities: Survey-based evidence - Nima Massarrat-Mashhadi; Christian Sielaff (International Journal of Economic Sciences and Applied Research, 2012)
Our paper assesses the accuracy of individuals' tax perceptions. Based on personal interviews, we aim to find out how tax complexity affects the capability of respondents to calculate income tax liability. Tax complexity is measured by interacting multiple tax rates, applied to one or more tax bases. Empirical results question the traditional view of taxpayers having a comprehensive understanding of taxation rules. Our findings support the view that increasing complexity affects the capability of taxpayers to accurately calculate income tax liability. For tax policy, there is also a need to determine how taxpayers erroneously deviate in terms of extent and direction, when facing increasing tax complexity. Our research design allows us to analyze extent and possible direction of the calculation bias. Approximating an empirical distribution of erroneous calculated effective tax rates could be helpful to design a more effective income tax system.
Keywords: C83; H21; H24; 330; tax complexity; survey data; estimated tax rates; Steuer; Einkommensteuer; Steuerbelastung; Steuertarif; Wahrnehmung